Partisipasi dan kepercayaan sosial daring: kebijakan vaksinasi COVID-19 di Indonesia - Baharuddin, Tawakkal; Sairin, Sjafri; Qodir, Zuly; Jubba, Hasse; Nurmandi, Achmad (Faculty of Communications Science, Dr. Soetomo University, 2022)
The vaccination policy is a government effort to reduce the number of COVID-19 cases in Indonesia. This study aims to determine the narrative, participation, and level of social trust in the vaccination policy in online social networks. Online social networks such as Twitter are the dominant media used during the pandemic period. As for the use of the Nvivo 12 Plus analysis software, the method was chosen to maximize the results of data coding from Twitter data sources. This study indicates that low social trust can hinder vaccination policies in Indonesia. This situation also affects the community's collective interest and cooperative attitude to support the government's efforts to reduce the number of cases of COVID-19 infection.